1980
DOI: 10.1149/1.2129533
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Polycrystalline Gold to the Hydrogen Electrode Reaction Promoted with Repetitive Potentiodynamic Perturbations

Abstract: The activation of gold electrodes toward the hydrogen electrode reaction is studied using the polycrystalline normalgold/1MH2SO4 interface at 25°C. The electrode activation is promoted by potentiodynamic aging in the potential range where the O‐electrosorption/O‐electrodesorption takes place. The activation effect is comparable to that earlier described when gold electrodes are cathodized for a relatively long time in the potential range of the net evolution of hydrogen. The activation effect is revealed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…By a recently introduced method using deposition and dissolution of PbO 2 in an alkaline medium, organic layers on the surface of gold nanoparticles can be easily removed without surface reconstruction [13,[27][28][29][30]. Furthermore, an additional advantage is that the surface features of the Au NPs can be accessed by studying the underpotential deposition (UPD) of lead, which is extremely sensitive to the surface structures of electrodes [13,30,41].…”
Section: Electrochemical Cleaning and Voltammetric Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…By a recently introduced method using deposition and dissolution of PbO 2 in an alkaline medium, organic layers on the surface of gold nanoparticles can be easily removed without surface reconstruction [13,[27][28][29][30]. Furthermore, an additional advantage is that the surface features of the Au NPs can be accessed by studying the underpotential deposition (UPD) of lead, which is extremely sensitive to the surface structures of electrodes [13,30,41].…”
Section: Electrochemical Cleaning and Voltammetric Characterizationmentioning
confidence: 99%
“…The first one is an electrochemical method. By repeated potential sweeping cycles in acidic or alkaline media with an upper potential higher than the potential for oxide formation [27,28], organic species can be eliminated. The second strategy is a thermal decomposition of organic molecules due to heat treatment [29].…”
Section: Introductionmentioning
confidence: 99%
“…Córdova O. et al the activity of gold electrode increases for hydrogen evolution reaction (HER) when gold electrode was subjected to the potentiodynamic perturbation (3). Similarly, Vuković M. et al has reported the increase in the activity of ruthenium for evolution of both Cl 2 and O 2 when ruthenium electrode was subjected to the anodic and cathodic potential cycling (4).…”
Section: Introductionmentioning
confidence: 98%
“…Proton reduction on Au has been studied extensively and described in detail. 279,[301][302][303][304][305][306][307] Here, pyridinium reduction is also examined via capacitance measurements for varying pH solutions as shown in Figure 5.4.10b. As the pH is lowered the original pyridine capacitive peak at -0.68 V decreases and shifts towards more positive potentials.…”
Section: Pyridiniummentioning
confidence: 99%